Transparent graphene bioelectronics as a new tool for multimodal neural interfaces. (June 2019) - Guan, Shouliang; Wang, Jinfen; Fang, Ying
Graphical abstract: Highlights: Transparent graphene bioelectronics enables multimodal neural interfaces. Graphene bioelectronics has been integrated with optical imaging. Graphene bioelectronics has been integrated with optogenetic stimulation. Abstract: A central challenge of neuroscience is to monitor the coordinated activity of neural circuits underlying information processing and behavior. Combining the advantages of electrical and optical modalities can provide unprecedented access to the spatiotemporal dynamics of neural activity. Transparent graphene bioelectronics has emerged as a suitable tool for the seamless integration of electrophysiological recording with optical imaging and optogenetic stimulation, opening up a variety of new opportunities in both neuroscience research and clinical applications.